“Que dicimos cando non falamos?” O silencio na comunicación - Rivas Rodríguez, Aitor (Madrygal. Revista de Estudios Gallegos, 2009)
“What do we say when we do not talk?” That is one of the questions we face when talking about silence. Our communicative output is a complex one; it is well know that speaking is just one of our elements of communication, as some others —such as the paralanguage, kinetics and even silence— are also important. This article focuses on the analysis of silence as an extremely important element to understand any communicative exchange. We shall see which its functions are and we shall study one example where silence does not exactly match stillness, i.e. the movement that affirms what verbal communication denies. The collection of my analysis intends to be a tiny approach to a multidisciplinar comunicative focus willing to set up the basis for the studies on non-verbal comunication for the Galician-speaking comunity.